Phase II studies of nebulised Arikace in CF patients with Pseudomonas aeruginosa infection - Clancy, J P; Dupont, L; Konstan, M W; Billings, J; Fustik, S; Goss, C H; Lymp, J; Minic, P; Quittner, A L; Rubenstein, R C; Young, K R; Saiman, L; et al. (Thorax, 2013)
Rationale Arikace is a liposomal amikacin preparation for aerosol delivery with potent Pseudomonas aeruginosa killing and prolonged lung deposition. Objectives To examine the safety and efficacy of 28 days of once-daily Arikace in cystic fibrosis (CF) patients chronically infected with P aeruginosa. Methods 105 subjects were evaluated in double-blind, placebo-controlled studies. Subjects were randomised to once-daily Arikace (70, 140, 280 and 560 mg; n=7, 5, 21 and 36 subjects) or placebo (n=36) for 28 days. Primary outcomes included safety and tolerability. Secondary outcomes included lung function (forced expiratory volume at one second (FEV1)), P aeruginosa density in sputum, and the Cystic Fibrosis Quality of Life Questionnaire—Revised (CFQ-R). Results The adverse event profile was similar among Arikace and placebo subjects. The relative change in FEV1 was higher in the 560 mg dose group at day 28 (p=0.033) and at day 56 (28 days post-treatment, 0.093L±0.203 vs −0.032L±0.119; p=0.003) versus placebo. Sputum P aeruginosa density decreased >1 log in the 560 mg group versus placebo (days 14, 28 and 35; p=0.021). The Respiratory Domain of the CFQ-R increased by the Minimal Clinically Important Difference (MCID) in 67% of Arikace subjects (560 mg) versus 36% of placebo (p=0.006), and correlated with FEV1 improvements at days 14, 28 and 42 (p<0.05). An open-label extension (560 mg Arikace) for 28 days followed by 56 days off over six cycles confirmed durable improvements in lung function and sputum P aeruginosa density (n=49). Conclusions Once-daily Arikace demonstrated acute tolerability, safety, biologic activity and efficacy in patients with CF with P aeruginosa infection.